Diversity and distribution of whiteflies colonizing cassava in eastern Democratic Republic of Congo - Casinga, C.M.; Wosula, E.N.; Sikirou, M.; Shirima, R.R.; Munyerenkana, C.M.; Nabahungu, N.L.; Bashizi, K.B.; Ugentho, H.; Monde, G.; Legg, James P. (MDPI, 2022)
The present study characterizes Bemisia tabaci and Bemisia afer from cassava in eastern Democratic Republic of Congo (DRC). The Mitochondrial COI sequencing revealed the occurrence of six cassava B. tabaci mitotypes, which were designated into four haplogroups (SSA-ECA, SSA-CA, SSA2, and SSA-ESA) using KASP SNP genotyping. SSA-ECA (72%) was the most prevalent and occurred in the northern part of the surveyed area, in the Ituri and Nord/Sud-Kivu provinces, whilst SSA-CA (21%) was present in the south, primarily in Haut-Katanga. SSA-ECA was predominant in the areas of north-eastern DRC most severely affected by cassava brown streak disease and was also reported in the new outbreak area in Pweto territory, Haut-Katanga, in the south. Bemisia afer comprised two major clusters with 85.5% of samples in cluster one, while the rest were in cluster two, which has no reference sequence in GenBank. This study provides important information on the genetic diversity of B. tabaci and B. afer in eastern DRC. This knowledge will be used as a basis for further studies to understand and to identify the role of whitefly haplogroups, their population densities and consequences for virus epidemics and spread as well as leading to improved vector and virus management strategies.